PENGARUH INOVASI PRODUK, CELEBRITY ENDORSEMENT, DAN ELECTRONIC WORD OF MOUTH TERHADAP MINAT BELI PRODUK KOSMETIK HANASUI (Studi Kasus Pada Masyarakat di Kabupaten Boyolali) - Tyas Wati Eka Safitri (STIE Wijaya Mulya, 2025)
The purpose of this study was to determine whether there is a partial and simultaneous influence of product innovation, celebrity endorsement, and electronic word of mouth on the purchase interest of Hanasui cosmetic products in the Boyolali Regency community. This type of research is quantitative research. This study uses primary data obtained from distributing questionnaires in the form of google forms distributed to 70 respondents. The population that is the object of this study is the community of Boyolali Regency. Sampling was carried out using purposive sampling techniques. The analysis techniques used are validity testing, reliability testing, multiple linear regression testing, coefficient of determination testing, and hypothesis testing using the SPSS version 27 program. The results of the study show that the calculation of the t test (partial test) of the product innovation variable has a significance value of 0.000 <0.005, the celebrity endorsement variable has a significance value of 0.040 <0.05, and the electronic word of mouth variable 0.334 >0.05, while the results of the F test calculation (simultaneous test) show a significance value of 0.000 <0.05. Based on the test results, it can be concluded that product innovation partially influences purchase intention for Hanasui cosmetic products, celebrity endorsement partially influences purchase intention for Hanasui cosmetic products, and electronic word of mouth partially has no effect on purchase intention for Hanasui cosmetic products. Simultaneously, product innovation, celebrity endorsement, and electronic word of mouth influence purchase intention for Hanasui cosmetic products. The adjusted R-square value is 42.9%, with the remaining 57.1% influenced by other variables. Product innovation has the most dominant influence on purchase intention for Hanasui cosmetic products. Keywords: Product Innovation (X1), Celebrity Endorsement (X2), Electronic Word of Mouth (X3), Purchase Intention (Y)